Pengaruh Komunikasi Keluarga Terhadap Motivasi Belajar Mahasiswa Generasi Z Universitas Telkom - Dhanisa, Andhira Surya; Aprianti, Agus (eProceedings of Management, 2024)
This research is taken from the phenomenon that Generation Z is in a transition phase, when parents still want tohave authority over their children, while children grow up wanting their own autonomy. All these changes affect thechild's self-worth and mood which has an impact on the interaction process with the family. Meanwhile, the familyhas an important role in forming values and norms in children. Then the indication of the problem found is thatGeneration Z has the characteristic of being lazy about learning because of digital distractions. This research aimsto find out whether there is an influence of family communication on the learning motivation of Generation Z studentsat Telkom University. This research uses quantitative methods by collecting 400 respondents from active studentsfrom the 2020 - 2023 class at Telkom University using an online questionnaire (google form). After carrying outcalculations, it was found that there was a significance value of 0.000 <0.05. From the results of the familycommunication hypothesis test, conversation orientation, t count 11,439 > t table 1,965. It can be concluded that H1is accepted and H0 is rejected, so there is a positive influence of conversation orientation patterns on the learningmotivation of Generation Z students at Telkom University. The conformity orientation communication patternobtained the hypothesis test results t count 11.507 > t table 1.965. So, it is concluded that H2 is accepted that there isan influence on conformity orientation family communication on the learning motivation of Generation Z students.From the percentage results calculated on the coefficient of determination, family communication influences thelearning motivation of Generation Z students at Telkom University by 47.3% while the remaining 52, 7% is influencedby other variables not included in this study. Keywords-family communication, conversation orientation, conformity orientation, learning motivation, generation z.